RE–OS ISOTOPE SYSTEMATICS FOR THE LINCE–ESTEFANíA DEPOSIT: CONSTRAINTS ON THE TIMING AND SOURCE OF COPPER MINERALIZATION IN A STRATABOUND COPPER DEPOSIT, COASTAL CORDILLERA OF NORTHERN CHILE - Tristá-Aguilera D.; Barra F.; Ruiz J.; Morata D.; Talavera-Mendoza O.; Kojima Sh.; Ferraris F. (My University, 2006)
The Lince–Estefanía stratabound copper deposit in the Michilla district is one of the most important deposits in the Coastal Cordillera of northern Chile and is one of the most representative of this type of deposit. Chalcocite and bornite characterize the main stage of hypogene copper sulfide mineralization. Rhenium and osmium isotopes are used here to constrain the age of hypogene mineralization and the source of osmium contained in these ore minerals. A Re–Os isochron yielded an age of 160±16 Ma (2σ), with an associated initial 187Os/188Os ratio of 1.06±0.09 (mean square of weighted deviates=1.8). This age is consistent with available geochronological data from volcanic rocks that host the mineralization and associated alteration phases. The high initial 187Os/188Os ratio indicates a lower crustal component for the source of Os and, by inference, the Cu sulfides that contain this Os. Late hematite occurs as an isolated phase or, more commonly, is associated with the chalcocite–bornite and supergene chalcocite–covellite associations. Analyses performed on pure hematite indicate a disturbance of the Re–Os system, and hence, this mineral phase is not useful as a Re–Os geochronometer.
Keywords: RE-OS ISOTOPES; STRATABOUND CU DEPOSITS; JURASSIC; COASTAL CORDILLERA; CHILE; Mesozoic::Jurassic; Мезозой::Юрская